Testes de vigor em sementes de quiabeiro - Lopes, Magnólia de Mendonça [UNESP] (2007)
The objective of this research was to study the physiological tests of controlled deterioration, accelerated aging, electrical conductivity and potassium leakage, for okra seeds, to evaluate it’s physiological quality. The experiment was carried out by using four okra seed lots cv. “Santa Cruz”. In the first stage were performed the standard germination, first germination count, speed of germination index, field seedling emergence, controlled deterioration seed (water content of 18, 21 and 24%, 45ºC, during 24 hours). The accelerated aging with and without salt solution with period of 48, 72, 96 and 120 hours at 41 and, 45ºC. For the electrical conductivity were used temperatures of 25 and, 30ºC, volumes of 25 and 50 mL of water, 25 and 50 seeds and periods of 1, 2, 4, 6, 12, 18 and, 24 hours. The potassium leakage (25 seeds, 25mL of water at 25ºC during 2, 4, 6, 12, 18 and 24 hours. In the second stage, the procedure considered more relevant for every test was repeated. According to the obtained results was concluded that the controlled deterioration test with 24% of seed water content at 41ºC for 24 hours. The accelerated aging with and without salt solution using 41ºC for 72 hours and the electrical conductivity test 25 seeds with 25mL of water at 25ºC during 24 hours were the most indicated tests to evaluate the physiological seed quality of okra seeds. The potassium leakage needs additional studies to adequate it’s methods and to make viable it’s use for okra seeds.